COMPARATIVE EFFICACY OF ANTICOAGULANT AND THROMBOLYTIC THERAPY IN PATIENTS WITH ACUTE THROMBOSIS OF THE INFERIOR VENA CAVA - Okley, D. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
138 patients with thrombosis in the system of the inferior vena cava was examined and treated. Thrombolytic therapy (TLT) as a basic method of treatment was used in 52 (37,7 %) patients. Of these, 20 (14,5 %) was performed catheter-controlled thrombolysis and 32 (23,2 %) patients had systemic thrombolytic therapy. The 86 (62,3 %) patients in the basic treatment had anticoagulant therapy (ACT). In the long-term results of thrombolytic therapy significantly exceed the results of ACT. The 70 % of this patients had signs of postthrombotic disease with mild chronic venous insufficiency, and 100% of patients with ACT had more forms of postthrombotic disease.